Molecular characterization of Escherichia coli 0149 and 0157 serotyyes isolated from piglets and poultry - Shome, B R; Shome, Rajeswari; Das, A; Mazumder, Y; Rahman, M M; Rahman, H; Murugkar, H V; Kumar, Ashok; Bujarbaruah, K M (The Indian Journal of Animal Sciences, 2005)
Escherichia coli strains (6) belonging to serotypes 0149(14) and 0157 (2), isolated from poultry and piglets suffering from colibacillosis were studied for their molecular characterization. All the E. coli isolates produced haemolysin in 10% cattle and goat blood agar. Both the E coli 0157 isolates were congo red binding positive. Four plasmid patterns having multiple plasmids (3-6) in the range of 4.5-60.0kb in each of the E coli isolates with a common plasmid of molecular size 23.1 kb were observed. All the poultry strains irrespective of serotype were negative for stx and hly genes. one strain each from Pig belonging to 0149 harboured stxl and hlya genes.In RAPD analysis, out of the 20 primers . OPG-8 and 9 gave reproducible and scorable amplicon profiles for all the E coli isolates belonging to both 0157 and 0149 serotypes. All the E coli isolates of 0149 serotype irrespective of source of isolation were having idential RAPD pattern and clustered in 1 genotype. All the isolates were resistant to ampieillum,cloxacillin, tetracycline and doxycycline but sensitive to ciprofloxacin.